Varicella-Zoster Virus Glycoprotein M Homolog Is Glycosylated, Is Expressed on the Viral Envelope, and Functions in Virus Cell-to-Cell Spread - Yamagishi, Yoshiaki (American Society for Microbiology (ASM), 2008)
Although envelope glycoprotein M (gM) is highly conserved among herpesviruses, the varicella-zoster virus (VZV) gM homolog has never been investigated. Here we characterized the VZV gM homolog and analyzed its function in VZV-infected cells. The VZV gM homolog was expressed on virions as a glycoprotein modified with a complex N-linked oligosaccharide and localized mainly to the Golgi apparatus and the trans-Golgi network in infected cells. To analyze its function, a gM deletion mutant was generated using the bacterial artificial chromosome system in Escherichia coli, and the virus was reconstituted in MRC-5 cells. VZV is highly cell associated, and infection proceeds mostly by cell-to-cell spread. Compared with wild-type VZV, the gM deletion mutant showed a 90% reduction in plaque size and 50% of the cell-to-cell spread in MRC-5 cells. The analysis of infected cells by electron microscopy revealed numerous aberrant vacuoles containing electron-dense materials in cells infected with the deletion mutant virus but not in those infected with wild-type virus. However, enveloped immature particles termed L particles were found at the same level on the surfaces of cells infected with either type of virus, indicating that envelopment without a capsid might not be impaired. These results showed that VZV gM is important for efficient cell-to-cell virus spread in cell culture, although it is not essential for virus growth.